Laparoscopic versus hybrid approach for treatment of incisional ventral hernia: a prospective randomised multicentre study, 1-year results - Mirella Ahonen-Siirtola; Terhi Nevala; Jaana Vironen; Jyrki Kössi; Tarja Pinta; Susanna Niemeläinen; Ulla Keränen; Jaana Ward; Pälvi Vento; Jukka Karvonen; Pasi Ohtonen; Jyrki Mäkelä; et al. (Springer New York LLC, 2022)
Purpose Laparoscopic incisional ventral hernia repair (LIVHR) is often followed by seroma formation, bulging and failure to restore abdominal wall function. These outcomes are risk factors for hernia recurrence, chronic pain and poor quality of life (QoL). We aimed to evaluate whether LIVHR combined with defect closure (hybrid) follows as a diminished seroma formation and thereby has a lower rate of hernia recurrence and chronic pain compared to standard LIVHR.
Methods This study is a multicentre randomised controlled clinical trial. From November 2012 to May 2015, 193 patients undergoing LIVHR for primary incisional hernia with fascial defect size from 2 to 7 cm were recruited in 11 Finnish hospitals. Patients were randomised to either a laparoscopic (LG) or a hybrid (HG) repair group. The main outcome measure was hernia recurrence, evaluated clinically and radiologically at a 1-year follow-up visit. At the same time, chronic pain scores and QoL were also measured.
Results At the 1-year-control visit, we found no difference in hernia recurrence between the study groups. Altogether, 11 recurrent hernias were found in ultrasound examination, producing a recurrence rate of 6.4%. Of these recurrences, 6 (6.7%) were in the LG group and 5 (6.1%) were in the HG group (p > 0.90). The visual analogue scores for pain were low in both groups; the mean visual analogue scale (VAS) was 1.5 in LG and 1.4 in HG (p = 0.50). QoL improved significantly comparing preoperative status to 1 year after operation in both groups since the bodily pain score increased by 7.8 points (p < 0.001) and physical functioning by 4.3 points (p = 0.014).
Conclusion Long-term follow-up is needed to demonstrate the potential advantage of a hybrid operation with fascial defect closure. Both techniques had low hernia recurrence rates 1 year after operation. LIVHR reduces chronic pain and physical impairment and improves QoL.